KEPATUHAN KOPERASI DIKOTA SEMARANG DALAM MEMBUAT LAPORAN PROMOSI EKONOMI - Warno, Warno (JURNAL STIE SEMARANG, 2012)
Of  the  data  showed that the cooperative's annual  financial  reports,  especially reports of net income, statement of changes in equity, the balance sheet generally docile but for the cash flow statement, statement of economic promotion and calendar notes the financial statements are still many who do not comply with accounting standards (GAAP) .   From these results it can be concluded cooperatives are still not able to understand what  the  benefits  of  compliance  with  the  financial  reporting  that,  in  fact  it  can  be concluded also cooperatives are still not able to calculate how much benefit from the presence of the members of the cooperative.   Promotion of economic reports that will be in seen how much benefit terhdap cooperative members, in addition to the co-operative has a special characteristic of the members for the members to members, in order to realize the special features then one way to understand the results by looking at the economic promotion reports